Synthesis of 1,5-Benzodiazepines Catalyzed by Zinc Triflate in Solvent-Free Medium - Ramesh Kumar, S.; Venkateshwarulu, Y.; Leelavathi, P. (Asian Journal of Chemistry, 2010)
The o-phenylenediamines were smoothly reacted with different ketones to afford the corresponding 1,5-benzodiazepine derivatives in excellent yields. All the reactions were carried out in presence of air and moisture stable zinc triflate (10 % mol) catalyst in solvent-free medium at room temperature.